Pencucian material magnetik pasir besi lansilowo menggunakan larutan asam klorida - Ricka Prasdiantika; Susanto Susanto (Universitas Gadjah Mada, 2020)
Iron sand was widely used in various fields such as in the manufacturing of magnets, cement, and steel. Iron sand has the main composition of iron oxide and several impurities of oxides. To remove these impurities, iron sand needs to be washed with acidic solution such as HCl solution. This study aims to minimize impurities in the magnetic material of Lansilowo iron sand. Iron sand was prepared using an external magnet to obtain magnetic material. The magnetic material was washed using distilled water and 0.5 M HCl solution. The drying process was carried out at 80oC for 24 hours. Magnetic material was crushed, weighed, and characterized. Material characterization was carried out using X-Ray Fluorescence (XRF), Fourier Transform Infrared (FT-IR) Spectrophotometer, and X-Ray Diffractometer (XRD). The Characterization results showed that washing of magnetic material using H2O-HCl 0.5 M was able to increase the percentage of Fe element composition in Lansilowo iron sand. The iron oxide contained in Lansilowo Iron Sand remains magnetite. The washing the iron sand magnetic material using 0.5 M HCl solution succeeded in removing impurities such as Mg, Pr, K, Cl, P, S, Co, Ce, and Sn as well as reducing the percentage of the Si and Al elements.The washing magnetic material using 0.5 M H2O-HCl produced higher XRD intensities than those washed with H2O. The washing magnetic material with 0.5 M H2O-HCl was result particle size of 37,70 ± 4,62 nm and crystallinity of 53.12%.